2017
DOI: 10.3390/e19110607
|View full text |Cite
|
Sign up to set email alerts
|

Fault Detection for Vibration Signals on Rolling Bearings Based on the Symplectic Entropy Method

Abstract: Abstract:Bearing vibration response studies are crucial for the condition monitoring of bearings and the quality inspection of rotating machinery systems. However, it is still very difficult to diagnose bearing faults, especially rolling element faults, due to the complex, high-dimensional and nonlinear characteristics of vibration signals as well as the strong background noise. A novel nonlinear analysis method-the symplectic entropy (SymEn) measure-is proposed to analyze the measured signals for fault monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 47 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…According to the probability of each state, the entropy of each of the wavelet sub-images can be calculated as in (19):…”
Section: Extraction Of Entropy Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the probability of each state, the entropy of each of the wavelet sub-images can be calculated as in (19):…”
Section: Extraction Of Entropy Featuresmentioning
confidence: 99%
“…Immovilli, Bellini, Rubini and Tassoni also compared the vibration-based method with the current-based method, and concluded that although the current-based method is suitable only for low-frequency working conditions, the vibration-based method is suitable for both low-and high-frequency working conditions [17]. Lei and Meng proposed the Symplectic Entropy method with Radial Basis Function (RBF) classifier for vibration-based defect classification for four conditions: normal condition, outer race defect, rolling element defect and inner race defect, and achieved 99.8% test accuracy with 6,000 vibration samples [19]. In more recent research, Li, Wang, Si and Huang applied an entropy-based defect classification method to the same data used in our research, and achieved 98.75% accuracy for ball defect detection and 100% accuracy for inner and outer race defect detection [20].…”
Section: Introductionmentioning
confidence: 99%